Latin America and Eastern Europe. Ideas for Historical Comparisons - Klaus Buchenau (Токови историје)
This article compares state and nation building in Latin America with Eastern Europe, including the Balkans. It comes to the conclusion that different imperial legacies (land empires vs. maritime empires) have led to different interpretative paradigms of understanding the world, with national/ethnic problems dominating the literature in and on Eastern Europe, whereas a social and post-colonial paradigm has become the dominant key of self-understanding in Latin America. As one of the consequences, the terms „left“ and „right“ do not have the same meaning in both regions. The article concludes with outlining a research agenda for further comparative work.